Mechanisms of nitrogen aggregation in nickel- and cobalt-containing synthetic diamonds - Nadolinny, V; Yelisseyev, A; Baker, M; Twitchen, D; Newton, M; Feigelson, B; Yuryeva, O (Elsevier, 2000)
We present a study of the point defects observed in as-grown and annealed synthetic diamonds using electron paramagnetic resonance (EPR) and infrared spectroscopy. The diamonds were grown by the temperature gradient HPHT method in a split sphere apparatus using Fe-Ni-C or Fe-Co-C solvent catalysts at 1700 K and 5.5 GPa. We report for the first time the observation of the nitrogen-vacancy (W15) and W33 EPR centres in as-grown and annealed nickel- and cobalt-containing diamonds. The generation of interstitials and vacancies on transformation of substitutional nickel Ni-s(-) into the NE4 defect with the structure of a double semivacancy, and on the reverse transformation, respectively, and the existence of different charge states of nickel and nitrogen defects, are reasons for aggregation of nitrogen at low annealing temperature. Most of the Ni; is transformed into Ni-N complexes in the temperature range 1600-1900 K. Nitrogen aggregation observed at higher annealing temperatures is due to a third mechanism by enhancement of the mobility of Ni by the Coulomb field of negatively charged nickel-containing centres. Charge transfer induced by X-ray irradiation indicated the existence of nearest-neighbour N-N+ and separated nitrogen pairs N---N+ in diamonds. The decreasing content of neutral and positive charge states of nitrogen on X-ray irradiation is due to charge transfer processes between Ni-s(-), P1, A-centres and separated P1 pairs. (C) 2000 Elsevier Science S.A. All rights reserved.